2010
DOI: 10.5012/bkcs.2010.31.02.275
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization of the Omp1-like Protein from Actinobacillus actinomycetemcomitans

Abstract: Actinobacillus actinomycetemcomitans is a gram-negative, nonmotile coccobacillus bacterium that is associated with several human diseases, including endocarditis, meningitis, osteomyelitis, subcutaneous abscesses and periodontal diseases. A full-length Omp1-like protein gene from A. actinomycetemcomitans was cloned into a pQE30 vector and overexpressed in Escherichia coli BL21(DE3) cells. The protein revealed sequence homologies to Seventeen kilodalton proteins (Skp) from Pasteurella multocida and E. coli that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This matched the pH of the buffer used for elution. 30,31 The folding properties of both the IGFBP-5 and TNFR1 proteins were characterized by CD spectroscopy. To determine the natures of the secondary structural elements of IGFBP-5 and TNFR1, far-UV CD spectra were recorded and analyzed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This matched the pH of the buffer used for elution. 30,31 The folding properties of both the IGFBP-5 and TNFR1 proteins were characterized by CD spectroscopy. To determine the natures of the secondary structural elements of IGFBP-5 and TNFR1, far-UV CD spectra were recorded and analyzed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B). [16][17] DSC scans were performed for conditions under which the protein was irreversibly unfolded. The temperature for minimal heat absorption by the protein was -0.9 o C. In our study, the protein showed no thermal transitions or denaturation from 0 o C up to 90 o C. In the present study, we measured the stability and conformational changes of recombinantly purified PsbS protein using various biochemical and biophysical techniques, including CD, DSC, and fluorescence measurements.…”
Section: Resultsmentioning
confidence: 99%